Dose-Painted Intensity Modulated Radiation Therapy Improves Local Control for Locally Advanced Pancreas Cancer. (18th October 2012) - Tunceroglu, Ahmet; Park, Joo Han; Balasubramanian, Sairam; Poppe, Matthew; Anker, Christopher J.; Poplin, Elizabeth; Moss, Rebecca A.; Yue, Ning J.; Carpizo, Darren; Gannon, Christopher J.; Haffty, Bruce G.; Jabbour, Salma K.
Abstract : Background . To evaluate the outcomes, adverse events, and therapeutic role of Dose-Painted Intensity-Modulated Radiation Therapy (DP-IMRT) for locally advanced pancreas cancer (LAPC). Methods . Patients with LAPC were treated with induction chemotherapy (n = 25 ) and those without metastasis (n = 20 ) received DP-IMRT consisting of 45 Gy to Planning Treatment Volume 1 (PTV1) including regional lymph nodes with a concomitant boost to the PTV2 (gross tumor volume + 0.5  cm) to either 50.4 Gy (n = 9 ) or 54 Gy (n = 11 ) in 25 fractions. DP-IMRT cases were compared to three-dimensional conformal radiation therapy (3D-CRT) plans to assess the potential relationship of radiation dose to adverse events. Kaplan-Meier and Cox regression analyses were used to calculate survival probabilities. The Fisher exact test and t -test were utilized to investigate potential prognostic factors of toxicity and survival. Results . Median overall and progression-free survivals were 11.6 and 5.9 months, respectively. Local control was 90%. Post-RT CA-19-9 levels following RT were predictive of survival (P = 0.02 ). Grade 2 and ≥grade 3 GI toxicity were 60% and 20%, respectively. In comparison to 3D-CRT, DP-IMRT plans demonstrated significantly lower V45 values of small bowel (P = 0.0002 ), stomach (P = 0.007 ), and mean liver doses (P = 0.001 ). Conclusions . Dose-escalated DP-IMRT offers improved local control in patients treated with induction chemotherapy for LAPC. Radiation-related morbidity appears reduced with DP-IMRT compared to 3D-CRT techniques, likely due to reduction in RT doses to organs at risk.